Wyłudzenia odszkodowań w ubezpieczeniach komunikacyjnych - Majewski, Piotr (Obtaining Motor Insurance Indemnities Under False Pretences, 2008)
The characteristic of motor insurance causes that this type of insurance is very suspectible to frauds. The main reason of that situation is: the type of insured object and the range of covered risks. The perpetrators of insurance frauds can obtain indemnities under false pretences, without having any sophisticated knowledge or incuring the risk of a penalty. They simply use regulation gaps. The aim of this paper is to present the analysis of insurance criminality in motor insurance. This analysis is the result of research project in which the biggest Polish insurance companies participated. The analysis includes the estimation of insurance criminality scale considering various types of methods used by the perpetrators. The research results are also compared with data collected from the Polish police and insurance companies. The conclusions presented in this paper are also a result of the author's professional experience in motorization and insurance branch.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 220-228